2017
DOI: 10.1016/j.apenergy.2017.05.076
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated microgrid investment and planning process considering the system operator

Abstract: Nowadays, a significant number of distribution systems are facing problems to accommodate more photovoltaic (PV) capacity, namely due to the overvoltages during the daylight periods. This has an impact on the private investments in distributed energy resources (DER), since it occurs exactly when the PV prices are becoming attractive, and the opportunity to an energy transition based on solar technologies is being wasted. In particular, this limitation of the networks is a barrier for larger consumers, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Another utility study [4] reveals that reduction in distribution line losses can only be achieved by targeted PV installation at specific locations. Involving the distribution system operator in such planning studies has also been encouraged in [5] to increase utility profits by optimal placement of distributed generators, and in [6] to elevate PV hosting capacity of microgrids while reducing network-related overvoltages. The work in [7] points out that installation of PV systems is motivated by distribution grid efficiency mandates and goes on to explore the financial perspectives of utilities and customers in determining optimal PV locations and sizes.…”
Section: Motivation and Contextmentioning
confidence: 99%
“…Another utility study [4] reveals that reduction in distribution line losses can only be achieved by targeted PV installation at specific locations. Involving the distribution system operator in such planning studies has also been encouraged in [5] to increase utility profits by optimal placement of distributed generators, and in [6] to elevate PV hosting capacity of microgrids while reducing network-related overvoltages. The work in [7] points out that installation of PV systems is motivated by distribution grid efficiency mandates and goes on to explore the financial perspectives of utilities and customers in determining optimal PV locations and sizes.…”
Section: Motivation and Contextmentioning
confidence: 99%
“…According to the research reported in the above references, the control variables of the system will feature an increasing amount of distributed renewable energy in the distribution network, which complicates the solution process, and is disadvantageous to the solution of the model. As a result of the continuous development of microgrid technology [20][21][22][23], experts and scholars in China and abroad studied the optimal dispatching problem of renewable energy in the form of microgrid access to a distribution network [24][25][26][27][28]. For example, Reference [27] considered the various interest demands of the microgrid and the distribution network, established a game relationship model of the two, proposed a cooperative evolutionary game algorithm to solve the above model, and achieved coordinated operation of the microgrid and the distribution network.…”
Section: Introductionmentioning
confidence: 99%
“…A two-level gaming approach was made for the optimal demand response management with multiple utilities and users [13]. The reinforcement learning is applied to find optimal power company selection [14].Many studies have been conducted to determine the optimal configuration of DERs in microgrids (MGs) [15][16][17][18][19][20][21]. The DER allocation problem can be formulated by a similar form of optimal sizing and placement problems because both problems involve choosing an optimal combination of DERs to maximize the revenue or minimize the expenses.…”
mentioning
confidence: 99%
“…The DER allocation problem can be formulated by a similar form of optimal sizing and placement problems because both problems involve choosing an optimal combination of DERs to maximize the revenue or minimize the expenses. The optimal placement of DERs in the MG are studied deterministically [15][16][17]. However, because the portfolio of a VPP cannot be changed frequently, the VPP operator needs to consider the long-term uncertainty of RESs.…”
mentioning
confidence: 99%
See 1 more Smart Citation